Trans tibial amputation with or without a tourniquet in patients with diabetic foot infection and peripheral vascular disease: Comparison of postoperative outcomes. (17th May 2022) - Gurel, Ron; Elbaz, Etay; Ashkenazi, Itay; Rotman, Dani; Factor, Shai; Chechik, Ofir; Warschawski, Yaniv; Albagli, Assaf
Background: Transtibial amputation (TTA) due to complications of diabetic foot infection (DFI) or peripheral vascular disease (PVD) is a high-risk procedure in fragile patients. The risks of reoperation, blood loss requiring blood transfusion, and mortality are high. The use of a tourniquet in this procedure is controversial and scarcely reported.Objective: this study aimed to compare the outcomes of TTAs with or without a tourniquet in a single tertiary medical center.Methods: We retrospectively identified all patients who had undergone TTA in our institution (1/2019-1/2020) and included only those who underwent the procedure due to complications of DFI or PVD ( n = 69). The retrieved data included demographics, comorbidities, ASA score, the use of a tourniquet, operation duration, pre- and postoperative hemoglobin levels, administration of blood transfusions, hospitalization length, surgical site infection and 60-days reoperation and mortality rates.Results: TTA with a tourniquet was superior to TTA without a tourniquet in reducing the average operation length by 11 min ( p = 0.05), the median postoperative hospitalization by 6 days ( p = 0.04), and the use of blood transfusions (odds ratio [OR] = 0.176, 95% confidence interval [CI]: 0.031–0.996).Conclusions: Our findings demonstrated advantages in operative time, hospitalization length, and blood transfusion requirement for TTA with a tourniquet compared to TTA without a tourniquet.